2011
DOI: 10.5761/atcs.oa.09.01427
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pleural Mesothelioma: Clinicopathologic and Survival Characteristic in a Consecutive Series of 40 Patients

Abstract: Introduction: Pleural malignant mesothelioma is an uncommon but extremely invasive tumor which originates from mesothelial cells and usually occurs after prolonged exposure to asbestos. Different types of surgical and oncological therapeutic methods have been used resulting in various outcomes. The aim of this study was to evaluate, clinicopathologically, 40 patients with pleural malignant mesothelioma and the main factors influencing their prognosis. Methods: In this study, 40 patients with a definitive diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
(17 reference statements)
0
8
1
Order By: Relevance
“…In our study, the percentage of patients aged 65 years or older was higher in the PNI-low group than in the PNI-high group (P = 0.019). Many studies had demonstrated that advanced age is an independent adverse predictor of survival for cancer patients [21,22] , but we failed to find the relationship between prognosis and age in our study cohort. The present study demonstrated that the PNI was significantly lower in patients with features of more advanced tumors, such as deeper depth of invasion and positive lymph node metastasis, than in those without such factors.…”
Section: Table 3 Univariate and Multivariate Cox Regression Analyses contrasting
confidence: 80%
“…In our study, the percentage of patients aged 65 years or older was higher in the PNI-low group than in the PNI-high group (P = 0.019). Many studies had demonstrated that advanced age is an independent adverse predictor of survival for cancer patients [21,22] , but we failed to find the relationship between prognosis and age in our study cohort. The present study demonstrated that the PNI was significantly lower in patients with features of more advanced tumors, such as deeper depth of invasion and positive lymph node metastasis, than in those without such factors.…”
Section: Table 3 Univariate and Multivariate Cox Regression Analyses contrasting
confidence: 80%
“…Moreover, Bagheri et al (2011) reported that while there was a significant relationship between survival and age, there was no significant relationship between survival and therapeutic plan. On the contrary, Akl et al (2010) reported statistically significant differences in survival time between patients subjected to different surgery, supportive treatment, chemotherapy and combined (chemotherapy and surgery).…”
Section: Discussionmentioning
confidence: 99%
“…In most industrialized countries, more than 90% of pleural mesotheliomas in men are related to prior asbestos exposure 11. On the other hand, only 25% of patients with malignant mesothelioma had a history of asbestos exposure in one study from Iran 20. In Korea, an average of 34 cases have been reported annually in the mesothelioma surveillance system data since 2001 21.…”
Section: Discussionmentioning
confidence: 99%